Nomogram to predict feasibility of minimally invasive interval debulking surgery in advanced ovarian cancer. Issue 4 (12th January 2022) - Conte, Carmine; Rosati, Andrea; Marchetti, Claudia; Iacobelli, Valentina; Quagliozzi, Lorena; Gallucci, Valeria; Gueli Alletti, Salvatore; Scambia, Giovanni; Fagotti, Anna
Abstract : Objective: Currently, there is no clear guidance defining the ideal candidate for minimally invasive interval debulking surgery. This study aimed to identify predictive factors for a minimally invasive approach in patients with advanced ovarian cancer who are candidates for interval debulking surgery after neoadjuvant chemotherapy. Methods: This was a single institution retrospective study conducted between January 2014 and June 2020 Perioperative variables were used to predict the likelihood of minimally invasive interval debulking surgery using multivariable models. A nomogram was developed, and internal validation was performed using the bootstrapping correction technique. This nomogram was built to visualize the effect of perioperative variables on the estimated probability of minimally invasive interval debulking surgery in patients with a clinical response after neoadjuvant chemotherapy. We used the four significant perioperative variables according to logistic regression. Results: A total of 108 (28.4%) and 272 (71.6%) patients underwent interval debulking surgery by a minimally invasive or open approach, respectively. Absence of omental cake (odds ratio (OR) 9.15, 95% confidence interval (CI) 4.26 to 19.64, p<0.001), high volume surgeon (OR 5.43, 95% CI 2.75 to 10.71, p<0.001), less than two peritoneal sites involved (OR 2.94, 95% CI 1.34 to 6.43, p=0.007), and CA125 normalization (OR 1.79, 95% CI 1.05 to 3.36, p=0.049) correlated with the feasibility of minimally invasive interval debulking surgery at multivariate analysis. The calibration plot demonstrated good agreement between the predicted and actual probability of minimally invasive interval debulking surgery (p=0.93, Hosmer–Lemeshow test). Conclusions: Our nomogram may serve as a useful tool to choose the surgical approach in patients with advanced ovarian cancer undergoing interval debulking surgery.